PEMBUATAN JAGUNG BOSE MAKANAN KHAS NTT SEBAGAI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI SDIT AL-MUTTAQIN KOTA KUPANG NTT - Dhajni, Arini Rahma (Universitas Nusa Cendana, 2023)
Kepmendikbudristek No.56/M/2022 concerning Guidelines for Curriculum Implementation in the Framework of Learning Recovery which states that the Curriculum Structure at the PAUD level and Primary and Secondary Education consists of intracurricular learning activities and projects to strengthen the profile of Pancasila students. Project activities to strengthen the profile of Pancasila students can be packaged with the theme of cultural food. Making bose corn which is a typical NTT food is an alternative in fostering Pancasila values that are packaged in P5 activities. This research includes descriptive qualitative research. This research provides an overview of the implementation of P5 activities at SDIT Al Muttaqin Kupang City. As a result, this activity can develop a student profile of Pancasila which includes dimensions of faith, fear of God Almighty, and noble character; Global diversity; Mutual cooperation; Independent; Critical thinking: and Creative.